Antibiotic ampicillin induces immune tolerance in renal transplantation by regulating the proportion of intestinal flora in mice - Wu, Xiaoqiang; Cao, Guanghui; Wang, Zhiwei; Wu, Xuan; Tian, Xiangyong; Gu, Yue; Shao, Fengmin; Yan, Tianzhong (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives There are significant differences in the composition of intestinal flora in renal transplant recipients before and after an operation, which has a great impact on the prognosis of renal transplantation. The purpose of this project is to study the effect of intestinal flora imbalance on renal transplantation. Methods The animal model of renal transplantation was established after intestinal flora imbalance (mice pretreated with compound antibiotics), or the animal model of renal transplantation was established after being pretreated with single antibiotics. HE, PAS, and Masson staining was used to detecting the histopathological changes of transplanted renal. The expression of inflammatory factors and infiltration of inflammatory cells of renal tissue were respectively been detected by ELISA kit and flow cytometry. Results Antibiotic pretreatment restored weight loss, and decreased serum creatinine level in mice after renal transplantation. The tissue staining, ELISA assay, and flow cytometry data showed that antibiotic pretreatment alleviated injury of the renal allograft, inhibited the inflammatory factors levels, and reduced inflammatory cell infiltration in mice after renal transplantation. Furthermore, single antibiotic, especially ampicillin pretreatment can also play the same role as compound antibiotics, such as restoring weight loss, decreasing serum creatinine level, alleviating renal allograft injury, inhibiting inflammatory factors levels, and reducing inflammatory cell infiltration in mice after renal transplantation. Conclusions Antibiotic ampicillin may inhibit inflammatory cell infiltration after renal transplantation by regulating the proportion of intestinal flora in mice, to reduce renal injury and play a role in renal protection.